3.3 kV SiC JBS diode configurable rectifier module - Mouawad, Bassem; Wang, Zhenyu; Buettner, J.; Castellazzi, Alberto (2017)
This paper presents the use of innovative high-voltage SiC diode technology in the development of a user configurable full-wave or half-wave rectifier bridge. The devices are of merged Junction-Barrier-Schottky (JBS) type to enable for optimum performance even in the presence of current surges, as demanded by the application. To contain the cost of the proposed solution, their packaging relies on Insulated Metal Substrates (IMS), as opposed to conventional ceramic type substrates. The layout and module pin terminations are chosen to yield optimum electro-thermal and electro-magnetic performance in compatibility with a standard solder and wire-bond assembly process. Preliminary functional static characterization tests at different temper¬atures are also presented.